Odpowiedzi

2009-11-29T11:50:52+01:00
Pierwistek z 7 odjac pierwiastek z 3
------------------------------------------------ =
pierwiastek z 7 dodac pierwistek z 3

(pierwistek z 7 odjac pierwiastek z 3)*(pierwiastek z 7 dodac pierwistek z 3)
-------------------------------------------------------
(pierwiastek z 7 dodac pierwistek z 3)*(pierwistek z 7 odjac pierwiastek z 3)

= 7-3
-------= 1
7-3
  • Użytkownik Zadane
2009-11-29T11:51:08+01:00
*pierwiastek z 3

pierwiastek z 7- 3
--------------------------------/pierwiastek z 7
pierwiastek z 7

7-3=4